Fornix transection selectively impairs fast learning of conditional visuospatial discriminations. - Kwok, S; Buckley, M (2010)
As the fornix has previously been implicated in the rapid learning of associations, we hypothesized that fornix transection in macaques would selectively impair the acquisition of rapidly learned conditional visuospatial discrimination problems. Macaque monkeys learned, postoperatively, three sets of concurrent problems of increasing sizes containing 8, 32, and 64 problems, respectively. Each problem consisted of four identical visual stimuli and animals had to learn which stimulus position was rewarded. The lesioned animals made significantly more errors-to-criterion on the smallest set of problems, consistent with the idea that the most rapidly acquired sets would be more vulnerable to fornical damage. Moreover, during the early stages of acquisition across all three sets, fornix transection selectively impeded monkeys' abilities to eliminate nonperseverative errors in correction trials, consistent with an inability to monitor or correct erroneous spatial responses made further back in time than the last trial. Both one-trial learning and an errorless learning (facilitation of performance) were observed in control and fornix lesioned animals but neither were fornix-dependent and overcoming the deleterious effect upon subsequent learning of having made prior errors was also unaffected by fornix transection. The data indicate that the fornix is not important for all forms of new learning; rather it is selectively concerned with the relatively rapid acquisition of spatial and temporal relationships between stimuli and responses.